2019
DOI: 10.3389/fchem.2019.00253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 4β-N-Acetylamino Substituted Podophyllotoxin Derivatives as Novel Anticancer Agents

Abstract: A series of novel podophyllotoxin derivatives obtained by 4β-N-acetylamino substitution at C-4 position was designed, synthesized, and evaluated for in vitro cytotoxicity against four human cancer cell lines (EC-9706, HeLA, T-24 and H460) and a normal human epidermal cell line (HaCaT). The cytotoxicity test indicated that most of the derivatives displayed potent anticancer activities. In particular, compound 12h showed high activity with IC 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…[60] Utilizing PPT and 4'-demethylpodophyllotoxin as precursors, a series of new PPT derivatives (159 a-m and 160 a-g) were synthesized by Wei et al Compounds 159 e-g showed outstanding activities against partial cancer cells and could induce apoptosis. [61] In summary, the chemical structures of promising derivatives against different cell lines were presented in Table 1.…”
Section: Structural Modifications At the C Ring Of Podophyllotoxinmentioning
confidence: 99%
See 3 more Smart Citations
“…[60] Utilizing PPT and 4'-demethylpodophyllotoxin as precursors, a series of new PPT derivatives (159 a-m and 160 a-g) were synthesized by Wei et al Compounds 159 e-g showed outstanding activities against partial cancer cells and could induce apoptosis. [61] In summary, the chemical structures of promising derivatives against different cell lines were presented in Table 1.…”
Section: Structural Modifications At the C Ring Of Podophyllotoxinmentioning
confidence: 99%
“…According to the structure-activity relationships (SARs) of PPT (Figure 8), the aryl tetralin skeleton was necessary for anticancer activity. [61] Previous structural modifica- tions of the A-ring of PPT resulted in derivatives with lower activity than PPT. And almost no modification of the A ring has been reported in recent years, indicating that the dioxolane ring (A ring) of PPT was essential for anticancer activities.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other genera such as Jeffersonia , Diphylleia , and Dysosma (Family Berberidaceae), Catharanthus (Apocynaceae), Polygala (Polygalaceae), Anthriscus (Apiaceae), Linun (Linaceae), Hyptis (Verbenaceae), Teucrium , Nepeta and Thymus (Labiaceae), Thuja , Juniperus , Callitris and Thujopsis (Cupressaceae), Cassia (Fabaceae), Haplophyllum (Rutaceae), Commiphora (Burseraceae), and Hernandia (Hernandiaceae) have also been reported to produce podophyllotoxin (PTOX) and its derivatives as well as other lignans [ 185 ]. Podophyllotoxin, 132 and deoxy-podophyllotoxin, 133 , both cyclolignans from the Anthriscus and Juniperus genera have shown excellent therapeutic effect on cancer cells with tubulin, and DNA topoisomerase II as potential targets ( Figure 26 ) [ 186 , 187 ].…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%